Bond slip modelling and its effect on numerical analysis of blast-induced responses of RC columns - Shi, Y.; Li, Z.; Hao, Hong (Techno Press, 2009)
Reinforced concrete (RC) structures consist of two different materials: concrete and steel bar. The stress transfer behaviour between the two materials through bond plays an important role in the load- carrying capacity of RC structures, especially when they subject to lateral load such as blast and seismic load. Therefore, bond and slip between concrete and reinforcement bar will affect the response of RC structures under such loads. However, in most numerical analyses of blast-induced structural responses, the perfect bond between concrete and steel bar is often assumed. The main reason is that it is very difficult to model bond slip in the commercial finite element software, especially in hydrodynamic codes. In the present study, a one-dimensional slide line contact model in LS-DYNA for modeling sliding of rebar along a string of concrete nodes is creatively used to model the bond slip between concrete and steel bars in RC structures. In order to model the bond slip accurately, a new approach to define the parameters of the one-dimensional slide line model from common pullout test data is proposed. Reliability and accuracy of the proposed approach and the one-dimensional slide line in modelling the bond slip between concrete and steel bar are demonstrated through comparison of numerical results and experimental data. A case study is then carried out to investigate the bond slip effect on numerical analysis of blast-induced responses of a RC column. Parametric studies are also conducted to investigate the effect of bond shear modulus, maximum elastic slip strain, and damage curve exponential coefficient on blast-induced response of RC columns. Finally, recommendations are given for modelling the bond slip in numerical analysis of blast-induced responses of RC columns.